Shibusa: extracting beauty - Adkins, Monty; Dickens, Pip (University of Huddersfield Press, 2012)
Shibusa - Extracting Beauty celebrates a number of artistic endeavours: music, painting and the skill of making in general with particular reflection upon Japanese aesthetics. Composer, Monty Adkins and visual artist, Pip Dickens (through a Leverhulme Trust Award collaboration) investigate commonality and difference between the visual arts and music exploring aspects of rhythm, pattern, colour and vibration as well as outlining processes utilised to evolve new works within these practices. The hand-cut paper Katagami stencil: a beautiful utilitarian object once used to apply decoration on to Japanese kimonos, is used as a poignant symbol - the 'hand-made machine' - by Adkins and Dickens both within the production of paintings and sound compositions and as a thematic link throughout the book. The book reviews examples of a number of contemporary artists and craftspeople and their individual approaches to 'making things well'. It explores the balance between hand skills and technology within a work's production with particular reference to Richard Sennett's review of material culture in The Craftsman. Shibusa - Extracting Beauty includes contributing essays by arts writer, Roy Exley, who examines convergence and crossover within the arts and an in-depth history, and review, of the kimono making industry by Kyoto designer, Makoto Mori.